The Use of Electronic Dictionaries for University students’ of STIT Muhammadiyah Tempurejo Ngawi - nining, nining nining (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
This paper presents a descriptive survey of the use of pocket electronic dictionaries (PEDs) by first-year university students at the Islamic Education Department of STIT Muhammadiyah Tempurejo Ngawi. The purpose was to explore general findings about the use of pocket electronic dictionaries and their impact on vocabulary-learning strategies of EFL students. Data were collected using a questionnaire and the results of their responses were tabulated. The participants were 75 students (50 females, 77.5% and 25 males, 22.5%) ranging in age from 18 to 30. The research population consisted of 25 students from four programs: PAI, PGMI, PIAUD and MPI. The findings revealed that students were not consistent in the use of any particular vocabulary strategy; furthermore, the students learned only a small number of words per week one to three words at the most according to their responses. PEDs were the most-used dictionaries, especially those installed on the students’ cellular phones, but printed dictionaries were still being used and some students preferred to use them in spite of having the electronic option. The results suggest that there is a need to promote proper and effective use of dictionaries, especially PEDs, to improve vocabulary learning. The experimental findings can help teachers and learners to enhance language learning by means of more precise and effective guidance and recommendations concerning the use of PEDs. Keywords: pocket electronic dictionaries, printed vs. electronic dictionaries, vocabulary-learning strategies